Centralidade urbana no Pontal do Triângulo Mineiro: um estudo sobre Frutal (MG) e Ituiutaba (MG) - Oliveira, Letícia Parreira (2015)
This study aims to understand the historical and socioeconomic formations from Frutal (MG) and Ituiutaba (MG) that lead to understand the relationships established today through the analysis of urban centrality in the context of Pontal do Triangulo Mineiro. The methodological steps enable to achieve the stated goal, considering that they permeated by theoretical research, secondary data and primary data in the field and in the City office. The bibliographic foundation was fundamental in the analysis, since the work already done helped in current research, contributing to the process of construction of categories used to assess the cities of Frutal (MG) and Ituiutaba (MG). The agricultural, agro-industrial, trade and services, franchising, health sector and higher education substantiate the study and helped achieve the comparative table between surveyed municipalities, as well as the study of the centrality. Thereby, it was possible to understand the distinctions and similarities between the two cities from the territorial formation identifying the dynamics of the Triangulo Mineiro (MG). Currently, the structuring elements of Frutal (MG) and Ituiutaba (MG) impact the socioeconomic dynamics and the urban centrality of each municipality. The highways, the polarization and flows identify the relationships between their hinterlands, and these are connected to the analysis categories, especially the health sector and higher education because its complexities in relation to the surrounding cities. Thus, the micro-regions of Frutal (MG) and Ituiutaba (MG) have small links, the ones that become more restricted when evaluating the headquarters municipalities. There are two islands, Frutal (MG) establishing relations with the state of São Paulo and Uberlândia (MG) and Uberaba (MG), and Ituiutaba (MG) that relates to the cities of its micro, some small in state of Goiás and Uberlândia (MG). In this context, the data allows us to understand the similar points and the existing distinctions between Frutal (MG) and Ituiutaba (MG), considering that they are different in territorial formation and the centralizing power, and similar in the agricultural bases, agribusiness, and the presence of political agents.